أثر فحص القوائم المالية المرحلية على سوق الأوراق المالية (من وجهة نظر المجتمع السوري) - سيدي عمر; مروه ربيع (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يدرس هذا البحث فحص القوائم المالية المرحلية للشركات المساهمة المدرجة في سوق الأوراق المالية في سورية وأثرها على ترشيد القرارات الاستثمارية في هذه السوق, حيث تم دراسة دور القوائم المالية المرحلية في توفير معلومات محاسبية دقيقة وسريعة تعكس الوضع المالي الحقيقي لهذه الشركات, وهذا يمكن المستثمرين من التنبؤ بصافي الربح السنوي وبالتالي العائد على أسهم هذه الشركات, فعملية فحص القوائم المالية المرحلية تزيد الثقة في هذه القوائم, فهي أداة للتأكد من قيام الشركة بالإفصاح الكافي والدقيق نسبياً على اعتبار أنها تتم من قبل مراجع حسابات خارجي مستقل. وبهدف اختبار فرضيات البحث تم توزيع استبانات على مجموعة من الأفراد ذوي الخبرة العلمية والعملية في مجال القوائم المالية المرحلية والاستشارات المالية السورية. This research studies reviewing of interim financial statements for companies listed in the securities market in Syria and its influence on the rationalization of investment decisions. So that it studied the role of interim financial statements in providing quick and accurate accounting information, reflecting the true financial position for these companies. This makes investors forecasting the annual net profit and the earnings per share for those companies. The interim financial statement reviewing increases the trust with these statements, because the operation of review is a device to check that the company did enough and relatively accurate disclosure, because this operation takes place by external and independent auditor. To test the research hypothesis, questionnaires was distributed to a group of individuals, who have academic and practical experience with the interim financial statements and financial consultancy in Syria.